Reproductive outcomes after hydatiform mole and gestational trophoblastic neoplasia. (2nd September 2015) - Gadducci, Angiolo; Lanfredini, Nora; Cosio, Stefania
Abstract: Gestational trophoblastic disease includes complete hydatidiform mole (CHM) or partial hydatidiform mole (PHM) and gestational trophoblastic neoplasia (GTN). Given the very high-curability rate of trophoblastic disease, the risk of further molar pregnancy after CHM or PHM as well as the risk of second primary tumors and fertility compromise after chemotherapy for GTN represent major concerns. The incidence of subsequent molar pregnancy ranges from 0.7 to 2.6% after one CHM or PHM, and is approximately 10% after two previous CHMs. Among patients who have received chemotherapy, there is an increased risk of myeloid leukemia which is mainly related to the cumulative dose of etoposide. Resumption of normal menses occurs in approximately 95% of women treated with chemotherapy, but menopause occurs 3 years earlier compared with those non-treated with chemotherapy. Term live birth rates higher than 70% without increased risk of congenital abnormalities have been reported in these women, and pregnancy outcomes are comparable to those of general population, except a slightly increased risk of stillbirth. Fertility-sparing treatment for placental site trophoblastic tumor is a therapeutic option reserved to highly selected, young women who do not present markedly enlarged uterus or diffuse multifocal disease within the uterus. Chinese abstract: 妊娠滋养细胞疾病包括完全性葡萄胎（CHM）或部分性葡萄胎（PHM）和妊娠滋养细胞肿瘤（GTN）。考虑到滋养细胞疾病的高治愈率，CHM或PHM后进一步葡萄胎妊娠的风险，以及GTN化疗后二次原发肿瘤和不孕的风险受到广泛关注。一次CHM或PHM后再次葡萄胎妊娠的发生率为0.7%至2.6%，2次CHM后发生率约为10%。接受化疗的患者发生粒细胞白血病的风险增加，这主要与依托泊苷的累积剂量有关。约有95%的女性在化疗后可恢复正常月经周期，但绝经年龄较未化疗者提前3年。这些女性的足月活产率高于70%且胎儿先天畸形风险并不增加，但死产风险轻度增加。胎盘部位滋养细胞肿瘤保留生育的治疗也是一种治疗选择，只适用于年轻女性无显著增大的子宫，或宫内无弥漫性多位点病灶者。